Si Canggih AI, antara Manfaat dan Ancaman, Pertahankan Ruang Menalar bersama Cendikia Muda SMP Negeri 1 Bangli - Keramas Pradnyana, Dewa Gede (Jayapangus Press, 2024)
Education is an activity that is consciously carried out and designed to achieve some set of goals. Education has a very noble goal; that is, to improve the quality of human resources, and one effort to improve human resources, in this case students, is through a learning process in which the formation of reasoning is carried out. Reasoning ability is one of the thinking skills that is very important for students. The ability to reason is closely related to solve a problem (problem solving). This ability is very important for students to have as a provision to solve everyday problems well. Learning must be adapted to the demands of the times so that students have the abilities and skills in the era when they grow and develop. The era of artificial intelligence requires the Alpha generation to be accustomed to high-level thinking. They are expected to be used to answering questions why, how, and being able to create or invent. The learning model for them is also chosen so that it can familiarize them with activities, namely experiencing, interacting, communicating and collaborating. In this way, students will get used to asking questions, expressing opinions, presenting results without fear or awkwardness. However, character building must still be considered to shape the Alpha generation's personalities into brilliant, polite, wise and self-confident individuals.